MANAGERIAL OPTIMISM AND DEBT FINANCING: CASE STUDY ON INDONESIA MANUFACTURING LISTED FIRMS - Gesti Memarista (Jurnal Keuangan dan Perbankan, 2016)
Managerials psychology can affect financial decision in the company. This paper analyzes the influence of managerial optimism on the debt financing by using regression analysis. The dependent variable in this paper is debt financing. The independent variable is managerial optimism and the control variable are firm value, firm size, and firm performance that are occurred in the previous period. The sample used in this study is manufacturing companies that listed in Indonesian stock exchange during 2010-2014. The result on this study shows that managerial optimism, firm value, and firm size that are occurred in the previous period have positive significantly impact on debt financing, whereas firm performance in the previous period has negative significantly impact on debt financing.